ï¡ - Semi-Regular Closed Sets - Mohammed, N. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, a new class of sets, namely ï¡- semi-regular closed sets is introduced and studied for topological spaces. This class properly contains the class of semi-ï¡-closed sets and is property contained in the class of pre-semi-closed sets. Also, we introduce and study ï¡srcontinuity and ï¡sr-irresoleteness. We showed that ï¡sr-continuity falls strictly in between semi-ï¡- continuity and pre-semi-continuity.